Analisis Pengembangan Kapasitas Masyarakat Pelaku Usaha Pariwisata Cottage di Fatumnasi Kabupaten Timur Tengah Selatan Nusa Tenggara Timur - Mantolas, Christina Mariana; Eky, Feny Susana; Lasibey, Ariance Ana; Liufeto, Marsen (Jurnal Ilmiah Pariwisata; Vol 30 No 1 (2025): Jurnal Ilmiah Pariwisata, 2025)
The community as cottage business actors can support survival through business activities. The aim of this research is to analyze the Capacity Development of Community Cottage Tourism Business Actors. Using four indicators, namely knowledge, skills, behavior and motivation. The research method uses a qualitative descriptive approach. The technique for determining informants uses purposive techniques. Data collection techniques use interviews, observation and documentation. The main findings are that business capacity development has been carried out by the relevant agencies such as the East Central South District Tourism Office and the East Nusa Tenggara Provincial Tourism Office through training programs, but has not been optimal in assisting and strengthening the community as Cottage business actors, while the skills possessed by the community are still minimal, related to community behavior and motivation are closely related, the community needs to improve themselves with the assistance of the relevant government agencies. And there is a need for motivation within business actors.  The findings of this research relate to aspects of human resources. Community involvement really supports the development of community capacity as business actors. Contribution as a researcher is to continue to provide motivation and enthusiasm for the best service to visiting guests, and continue to learn to improve knowledge and skills to support the development of human resources in the Fatumnasi Cottage business community. Keywords: c apacity development, cottage business actors